The Natural Filtration of Finite Dimensional Modular Lie Superalgebras of Special Type - Keli Zheng; Yongzheng Zhang (Abstract and Applied Analysis)
This paper is concerned with the natural filtration of Lie superalgebra S(n,m) of special type over a field of prime characteristic. We first construct the modular Lie superalgebra S(n,m). Then we prove that the natural filtration of S(n,m) is invariant under its automorphisms.